Efektivitas Pembelajaran Online pada Siswa Selama Pandemi Covid 19 di Era Literasi Digital - Arinah Fransori; Nur Irwansyah; Friza Youlinda Parwis (Departement of Mathematics Education, 2023)
The purpose of this research is to see how the online learning process for students, or children and society in the digital literacy era? How is it progressing? Can the children understand the learning process! Then what is the role of parents and their teachers in the learning process. The subjects of this study were children and their parents in Meruyung Village, Limo District, Depok, West Java. This research method is descriptive qualitative research with analytical descriptive approach. Data collection techniques used are interviews, observations / observations. The results of this study are in the form of data and information related to the effectiveness of online learning during the COVID-19 pandemic in the current digital literacy era.